Web 3.0 in the Hotel Sector of Murcia - Padilla-Piernas, Juana María; Parra-Meroño, M. Concepción; Beltrán-Bueno, Miguel Ángel (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
The Internet has revolutionised the way we communicate, and the tourism industry is one of the leading industries in terms of incorporating these elements into its websites. The purpose of this study is to analyse the degree of integration of 2.0 and 3.0 tools in hotel websites, as well as their evolution over a period of 10 years. The descriptive method is used to measure the degree of development of the websites and their evolution. It was found that hotels in the region of Murcia have gone beyond web 2.0 but still have to implement web 3.0.